Periodic event‐triggered control with multisource disturbances and quantized states. (4th May 2021) - Zhao, Mingyuan; Zheng, Shiqi; Ahn, Choon Ki; Zong, Xiaofeng; Zhang, Chuan‐Ke
Abstract: This study investigates periodic event‐triggered (PET) output‐feedback control method for nonlinear systems with quantized states and multisource disturbances. Based on a PET extended state observer, a novel PET composite control method is proposed. It not only can deal with the deterministic and stochastic disturbances but also can handle the quantization in the data transmission process. A PET extended state observer is used to simultaneously estimate the states and the disturbances. Moreover, both the static and dynamic event‐triggered conditions are considered. Simulations and an experiment on a direct current brush motor are conducted to validate the proposed approach.